Contextualization and Localization in Science Curriculum Implementation: A Systematic Review of Strategies, Impacts, and Challenges in the Philippine Basic Education System - Banzuelo, Je-Ann; Quiñones, John Rey B. (Future Science / FSH-PH Publications, 2026)
The K-12 Basic Education Program in the Philippines, institutionalized through Republic Act 10533 and operationalized by DepEd Order No. 35, s. 2016, mandates the use of Contextualization and Localization (C&L) to enhance the relevance of the science curriculum. This systematic review synthesizes literature from 2010 to 2024 to analyze the implementation, impacts, and challenges of C&L in Philippine science education. Findings reveal prevalent teacher-initiated practices, such as leveraging local biodiversity, integrating Indigenous Knowledge Systems (IKS), and employing community-based problem-solving. These strategies are consistently shown to improve student engagement, deepen conceptual understanding, and strengthen cultural identity. However, significant systemic barriers impede effective implementation, including inadequate teacher preparation, a lack of validated localized materials, large class sizes, rigid curriculum pacing, and epistemological tensions between indigenous and Western scientific paradigms. The review further identifies methodological limitations in the existing research, notably a predominance of small-scale qualitative studies, an absence of longitudinal data on learning outcomes, and insufficient inclusion of student and community voices. To realize the transformative potential of C&L for democratizing science education, this study calls for a multi-stakeholder approach involving reformed teacher education, sustainable support systems for resource development, and a robust research agenda focused on scalability, impact, and ethical knowledge integration.